SOSIALISASI KEUNGGULAN RELASIONAL YANG INTIM (Intimacy Relational Advantage) UMKM DESA TULEHU KAB MALUKU TENGAH - Rainier Hendrik Sitaniapessy, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service is carried out to answer the dynamics of the competitive environment, the COVID-19 pandemic and the Human Development Index (IPM) in Maluku province in Maluku province which has not been maximized. Small businesses (MSMEs) as the basis for community economic development are required to try to get out of a complex situation. Various reasons obtained from discussions and questions and answers in the form of discussions that illustrate the ability to find opportunities or entrepreneurship are still low so that we provide a comprehensive understanding related to the problems faced by SMEs in Tulehu Village. It is hoped that various problems can be overcome by providing ongoing assistance